Penerapan Metode Waterfall Dalam Rancang Bangun Sistem Informasi Penggajian Berbasis Web - Salsabila Putri Dinka; Zahra Putri Salsabilah; Lala Nilawati (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
The development of technology today demands several things, namely services that are getting easier, faster and more practical. A computer technology is needed by the company, which is used as a tool in solving work problems, such as in terms of processing payroll data. Payroll data processing at the company is included in a complicated problem, because if in the payroll calculation an error occurs in the calculation, it can be detrimental to both the company's management and employees. FoodPedia by Pasta Kangen is currently still doing payroll manually, which can be seen from the attendance recap process, salary calculation data, and report generation. This can be manipulated and can harm the company or employees. Based on this, this research will design a web-based payroll information system, using the Java Web programming language with Neatbeans 8.1 software and MySQL for database needs. The research method used is using data collection methods, and software development methods with the waterfall method. This payroll information system is equipped with various features such as an employee attendance recap menu, calculation of employee salary data, as well as data needed in the payroll process. This payroll system is expected to simplify and speed up the process of calculating employee salaries accurately, effectively, efficiently and transparently.